Alagille syndrome: Review of 14 patients - Purnamawati S. Pujiarto; Arnold L. Smith (Indonesian Pediatric Society Publishing House, 2017)
Alagille syndrome (AGS) Is a common form of familial intrahepatic choleslasis, an autosomal dominant disorder due to defects in Jagged1 gene. It Is characterized by at least 3 of 5 mator features. We reviewed two groups of patients with AGS. Group 1 comprised 12 AGS patients, retrospectively studied (1995-1996), in the Gastroenterology Department, Royal Children's Hospital, Melbourne. Group 2 comprised 2 AGS patients, prospectively studied since 1999, in The Pediatric Hepatology Division, Cipto Mangunkusumo Hospital, Jakarta. Prolonged cholestasis is the most common feature at presentation (12 patients). All these 12 subjects developed pruritus and xanthoma of varying degree. Osteopenia occured in 6 patients, 2 patients experienced fractures. AGS facies was noted In aH 14 subjects. Heart anomaty was found in 10 patients, vertebral anomaly in 6 patients, and posterior embryotoxin in 10 patients. Common additional features were growth and mental retardation in 10 and 8 patients, respectively. Liver biopsy was able to confirm the diagnosis as young as age 2 months. Death occurred in 2 patients due to liver failure and hemorrhagic pneumonia. Liver transplant was done in 1 patient due to poor quality of life (severe pruritus, xanthoma, recurrent fractures). Affected family members were strongly presumed in 8 patients. In conclusion, AGS should be considered in babies with chronic Intrahepatic cholestasls, especially it associated with pruritus. Liver biopsy Is the most sensitive diagnostic testing which will prevent unnecessary surgical intervention due to biliary atresia mimicry.